Kształcenie dziennikarzy w Islandii. Teoria i praktyka - Pokrzycka, Lidia (Zeszyty Prasoznawcze, 2015)
This paper describes the system of journalists’ training in Iceland (in theory and practice), on the basis of research and the author’s own experience. After a series of lectures at the University of Iceland, an internship in a popular Icelandic paper as well as teaching courses at Reykjavik University, it can be concluded that the training of journalists in Iceland is modern, tailored to the changing reality. However, it is the media market that decides whether the education is valuable. In case of Iceland, this market is too small to maintain full independence from political authorities and advertisers.